An Evidence-Based Checklist for Improving Scoping Review Quality. (March 2021) - Cooper, Simon; Cant, Robyn; Kelly, Michelle; Levett-Jones, Tracy; McKenna, Lisa; Seaton, Philippa; Bogossian, Fiona
A scoping review aims to systematically explore and map the research available from a wide range of sources. The objective of this study was to produce a scoping review checklist to guide future scoping studies to enable rigorous review and critique of phenomena of interest. The methods used included a review of literature, expert consensus group meetings, a modified Delphi survey and, finally, verification against recent scoping study examples. Results showed that the checklist was able to identify key elements of scoping reviews. The 22-item Scoping Review Checklist (SRC), which includes two optional stakeholder consultation items, has been developed using rigorous recommended approaches. The checklist can be used to guide the conduct and critique of scoping studies.